2001
DOI: 10.1002/1521-3749(200105)627:5<985::aid-zaac985>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Site Preference in Iron Tetracarbonyl Complexes Fe(CO) 4 L (L = CO, CS, N 2 , NO + , CN , NC , η 2 ‐C 2 H 4 , η 2 ‐C 2 H 2

Abstract: Equilibrium geometries, bond dissociation energies and relative energies of axial and equatorial iron tetracarbonyl complexes of the general type Fe(CO) 4 L (L = CO, CS, N2, NO + , CN ± , NC ± , g 2 -C 2 H 4 , g 2 -C 2 H 2 , CCH 2 , CH 2 , CF 2 , NH 3 , NF 3 , PH 3 , PF 3 , g 2 -H 2 ) are calculated in order to investigate whether or not the ligand site preference of these ligands correlates with the ratio of their r-donor/p-acceptor capabilities. Using density functional theory and effectivecore potentials wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 23 publications
7
27
0
Order By: Relevance
“…The metal centres in [LM(CO) 5 ][BPh 4 ] adopt a slightly distorted octahedral geometry and the iron atom in [LFe(CO) 4 ][BPh 4 ] adopts a trigonal bipyramidal geometry, whereby [L] + occupies an axial position. Some evidence has shown that σ‐donor ligands have a preference for axial site coordination in Fe(CO) 4 complexes and that strong π‐acceptors have a preference for the equatorial site (although there is some debate on the topic), suggesting that [L] + is most likely not an excellent π‐acceptor (as a comparison, the π‐acidic phosphenium cation (Et 2 N) 2 P + coordinates Fe(CO) 4 in the equatorial position) . The Fe−P and M−P bond lengths fall between those of zwitterionic triphosphenium–M(CO) 5 complexes (which are slightly shorter) and NHC‐phosphinidene‐adduct–M(CO) 5 complexes (which are slightly longer) .…”
Section: Resultsmentioning
confidence: 99%
“…The metal centres in [LM(CO) 5 ][BPh 4 ] adopt a slightly distorted octahedral geometry and the iron atom in [LFe(CO) 4 ][BPh 4 ] adopts a trigonal bipyramidal geometry, whereby [L] + occupies an axial position. Some evidence has shown that σ‐donor ligands have a preference for axial site coordination in Fe(CO) 4 complexes and that strong π‐acceptors have a preference for the equatorial site (although there is some debate on the topic), suggesting that [L] + is most likely not an excellent π‐acceptor (as a comparison, the π‐acidic phosphenium cation (Et 2 N) 2 P + coordinates Fe(CO) 4 in the equatorial position) . The Fe−P and M−P bond lengths fall between those of zwitterionic triphosphenium–M(CO) 5 complexes (which are slightly shorter) and NHC‐phosphinidene‐adduct–M(CO) 5 complexes (which are slightly longer) .…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with the observations in solution, the phosphorus atom occupies an axial position, which is preferred by ligands with strong s-donor and weak pacceptor abilities. [19] As was found for the chromium complex 3 the PÀM' interaction (M' transition metal) in 5 seems rather weak, and this leads to the longest PÀFe(CO) 4 bond (237.7(1) pm) reported so far (observed range for pentacoordinated iron: 216 ± 237 pm). [9] For the related complex [{(Me 3 -Si) 3 P}Fe(CO) 4 ] a PÀFe bond length of 233.8(4) pm was found.…”
Section: Resultsmentioning
confidence: 99%
“…Yield: 0.10 g (0. 19 ] (0.5 mmol; E P: 0.20 g; E As: 0.22 g, E Sb: 0.25 g) in pentane (20 mL). A smooth gas evolution was observed, and the resulting suspension was slowly warmed to room temperature.…”
Section: Methodsmentioning
confidence: 93%
“…The increasing order of above-mentioned r-donation is understood in terms of the percent of polarized electron toward the W center in the W-P r-bond, which decreases in the following manner: PF 3 (%37.61) ) P(Me) 3 (%32.56) > PCl 3 (%30.50) > PH 3 (%30.18) > PBr 3 (%30.08) > PI 3 (%29.33). This is in accord with the recent calculation by Frenking and coworkers [18] which showed donation of phosphine ligand in Fe(CO) 4 PF 3 to be higher than donation in Fe(CO) 4 PH 3 .…”
Section: Which Factors Are the Origin Of These Structural Preferencesmentioning
confidence: 99%
“…These ligands are important because their electronic and steric properties can be altered in wide range by varying R. The phosphines, in addition to r-donor property (via a hybrid orbital containing a lone pair on phosphorus) are also considered as double-face p-acceptors (via empty r à orbitals of the P-R bonds) in which the nature of the R group determines the relative donor/acceptor ability [15]. Recently, the theoretical studies have also been done on complexes containing phosphine ligands [16][17][18].…”
Section: Introductionmentioning
confidence: 99%